Effects of the Proprioceptive Neuromuscular Facilitation Contraction Sequence on Motor Skill Learning-Related Increases in the Maximal Rate of Wrist Flexion Torque Development - Green, Lara A.; McGuire, Jessica; Gabriel, David A. (Frontiers in Human Neuroscience, 2021)
Background: The proprioceptive neuromuscular facilitation (PNF) contraction reversal technique has the potential to increase the maximum rate of torque development as compared to simple, unidirectional contractions. Despite the more complex pattern, PNF contractions show similar motor learning gains. However, the neuromotor mechanisms contributing to these facilitated contractions and motor learning-related improvements remains unclear. Methods: Twenty-six participants completed isometric maximal extension-to-flexion (experimental PNF group) or flexion-only (control group) contractions at the wrist. Ten of the assigned contractions were performed on each of three sessions separated by 48-hours for skill acquisition. Retention was assessed with 10 contractions performed two-weeks after acquisition. Results: Wrist flexion torque and maximal rate of torque development was not significantly different between groups, increased comparably over the acquisition phase, and improvements were retained after two-weeks. The experimental group had increased torque variability, coactivation, and electromechanical delay values. However, both groups had similar decreases in these measures with acquisition resulting in no significant group × session interaction. The retention of these measures indicated that motor learning occurred in both groups, despite the more complex PNF contraction pattern. There were no significant differences between groups or across test sessions in the rate of muscle activation (Q30 ). Discussion: Surprisingly, the PNF contraction pattern did not facilitate an increased rate of torque development. However, the more complex pattern did not inhibit motor learning. The main adaptation in neuromotor control was a decrease in coactivation, and not the maximal rate of muscle activation.